2022
DOI: 10.1002/hec.4586
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soda taxes beyond beverages in Philadelphia

Abstract: Taxes on sugar sweetened beverages (SSBs) have been increasingly enacted in the United States (US) because of their links to negative health outcomes such as obesity and increased risk of suffering from diabetes and cardiovascular conditions (Colchero Nielsen's copyright of data: Copyright ⓒ 2022 The Nielsen Company (US), Limited Liability Company (LLC). All Rights Reserved. Researcher(s)' own analyses calculated (or derived) based in part on data from Nielsen Consumer LLC and marketing databases provided thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
2
4
1
Order By: Relevance
“…Our findings are also consistent with findings of net reductions of 22% of volume sold of taxed beverage and net reductions in added sugar purchased from beverages in Seattle and Philadelphia, which, if uncompensated, would be expected to result in improved BMI. 11,27,28 Our results are less consistent with findings from our previous longitudinal cohort study of taxed beverage consumption among lower-income children in Seattle and the nearby nontaxed comparison area. 29 In that study, we found no greater reduction in reported consumption for Seattle children vs those in the comparison area.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings are also consistent with findings of net reductions of 22% of volume sold of taxed beverage and net reductions in added sugar purchased from beverages in Seattle and Philadelphia, which, if uncompensated, would be expected to result in improved BMI. 11,27,28 Our results are less consistent with findings from our previous longitudinal cohort study of taxed beverage consumption among lower-income children in Seattle and the nearby nontaxed comparison area. 29 In that study, we found no greater reduction in reported consumption for Seattle children vs those in the comparison area.…”
Section: Discussioncontrasting
confidence: 99%
“…Whereas these studies had repeated cross-sectional designs, our study used longitudinal data from the same children over time, used measured height and weight, and implemented methods to robustly control for pretax differences in trends; thus, our study builds on and adds rigor to the evidence. Our findings are also consistent with findings of net reductions of 22% of volume sold of taxed beverage and net reductions in added sugar purchased from beverages in Seattle and Philadelphia, which, if uncompensated, would be expected to result in improved BMI …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At the population level, we estimate that a quarter of the caloric reduction from taxed beverages is compensated for by an increase in calories purchased from untaxed foods. This is close to the midpoint of Lozano‐Rojas and Carlin's (2022) quasi‐experimental estimates of between 19% and 37% of the reduction in beverage sugar in Philadelphia being offset by other sugary foods. At the subpopulation level, our simulation does indicate meaningful caloric compensations (63%–78%) among households without obese members, although substitution does not fully offset the direct effect of a sweetened beverage tax.…”
Section: Comparisons With Previous Literaturesupporting
confidence: 78%
“…In Mexico – a national jurisdiction – much of the substitution effects from a diet-related tax came from individuals purchasing untaxed unhealthy foods within Mexico, 96 while in smaller subnational jurisdictions such as Philadelphia in the United States, cross-border shopping was an important source of substitution for a similar tax. 113 An important issue remains the specific economic context of the jurisdiction in which the FP is considered. Jurisdictions with greater reliance on the sugar industry may be more vulnerable to the impacts of a tax on sugar or sugar-added products and thus politically more sensitive to measures that target them.…”
Section: Discussionmentioning
confidence: 99%